The Effect of Organic Insecticide and Various Cultivars on Attack Intensity of Spodoptera exigua and Results Shallots (Allium Ascalonicum L.) - Vivi Erfhia Rachmawati; M. Syamsul Maarif; Maharani Maharani; Deden Deden; Dukat Dukat; Uum Umiyati (Eduvest - Journal of Universal Studies, 2023)
The use of chemical insecticides to control Spodoptera exigua is currently the main choice for farmers. The continuous use of chemical insecticides will cause many problems including resistance, food safety and environmental damage. alternative use of organic insecticides needs to be applied for the control system of Spodoptera exigua on shallot plants. The experiment was carried out in Playangan Village, Gebang District, Cirebon Regency, in April-June 2019. The research method used a randomized block design with 3 replications, consisting of 9 treatment combinations of three cultivars: Bima, Ilokos, Sumenep, organic insecticides: neem seed extract, Bauveria bassiana, Bacillus thuringiensis. The results of the experiment showed that the combination of treatment of 3 cultivars of shallots and organic insecticides had a significant effect on the components of the intensity of the attack of Spodptera exigua pests (plants aged 43, 50 and 57 DAP). The best treatment was obtained, namely the treatment of Ilokos cultivar and neem seed extract insecticide with tuber yields of 6.60 kg / plot or equivalent to 28.57 tonnes / ha.